Claims of misoprostol use based on blood sampling should be viewed with skepticism. Issue 2 (27th August 2014) - Frye, Laura J.; Winikoff, Beverly; Meckstroth, Karen
Abstract: Efforts to prosecute women for induced abortion have included allegations that misoprostol was found in body fluids. These claims, however, are questionable owing to the timing of specimen collection for accurate results, the scarcity and expense of validated assays, and the onerous lab procedures required to determine the presence of the substance. Adequate scrutiny should be applied each time such a claim is made.